2015
DOI: 10.4141/cjps-2014-127
|View full text |Cite
|
Sign up to set email alerts
|

Induction and resistance against Fusarium wilt disease of tomato by using sweet basil (Ocimum basilicum L) extract

Abstract: Akladious, S. A., Isaac, G. S. and Abu-Tahon, M. A. 2015. Induction and resistance against Fusarium wilt disease of tomato by using sweet basil (Ocimum basilicum L) extract. Can. J. Plant Sci. 95: 689Á701. The antifungal activity of Ocimum basilicum (sweet basil) extract against Fusarium oxysporum f. sp. lycopersici race 3 the causal agent of tomato wilt and its ability in inducing disease resistance were studied in vivo using seed-soaking treatment before sowing. Plants were harvested at 45 and 105 d (vegetat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…Two new protein bands at molecular weight 47.2 KD and 16.3 KD were appeared in all infected plants treated with Bio-Zeid and Bio-Arc while, not appeared in the control plants. These results are in agreement with those reported by El-Askary et al (2003) and Akladious et al, (2015). They showed that new protein bands induced in infected plants treated with the bio-products act as a protein marker in resistance mechanisms; such response allows plants to become more tolerant to the pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…Two new protein bands at molecular weight 47.2 KD and 16.3 KD were appeared in all infected plants treated with Bio-Zeid and Bio-Arc while, not appeared in the control plants. These results are in agreement with those reported by El-Askary et al (2003) and Akladious et al, (2015). They showed that new protein bands induced in infected plants treated with the bio-products act as a protein marker in resistance mechanisms; such response allows plants to become more tolerant to the pathogens.…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that PPO1 was present in the latent form in roots of younger seedlings and was activated during development. Moreover, CAN, similar to other stress factors [ 72 ], stimulated the activity of both isoforms after 72 h treatment.…”
Section: Discussionmentioning
confidence: 64%
“…Biological control is becoming increasingly important in integrated pest management programs, especially when discussing integrated production towards sustainable agriculture. Many plant and plant extracts have been reported to have antimicrobial properties against plant pathogenic fungi (Sharmin et al, 2013;Vergnes, 2014;Akladious et al, 2015;Santos et al, 2015). Allamanda species extract has been proved as effective in controlling plant pathogenic fungi (Islam, 2004;Ravikumar et al, 2013;Basar et al, 2011;Mone et al, 2013;Barros et al, 2015;Brito et al, 2018).…”
Section: Discussionmentioning
confidence: 99%